Analisis Indeks Kepuasan Masyarakat dalam Upaya Peningkatan Kepuasan Kualitas Pelayanan Masyarakat di Kantor Kecamatan Kotabaru Kabupaten Karawang - Rizka Mardiyanto; Mary Ismowati (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
People need services to meet a variety of needs that can not be fulfilled themselves. Similarly, at the Kotabaru District office, Karawang regency, West Java province has an important role to provide public services. The main purpose of public service is the satisfaction of the community. This satisfaction can be realized if the services provided in accordance with service standards established or better than the standard service. The services provided in general have not satisfied the public.The purpose of this study is to analyze the value of the level of Satisfaction Index in Kotabaru District Karawang regency in an effort to increase the quality of service satisfaction in Kotabaru district office Karawang regency.The research approach is quantitative. Technique sampling technique proportionate stratified random sampling. Population 18,584 People with 207 samples. Data collection techniques with questionnaires. Technique Data analysis is Satisfaction Index of Society based on Rating of service quality KEP / 25 / M.PAN / 2/2004 about General Guidance of Compilation of Public Satisfaction Index.Based on the result of calculation of Satisfaction Index of Public in Kotabaru Subdistrict office with acquisition value of Satisfaction Index of Community equal to 54,10 quality of Kotabaru District office service performance is at "C" level of bad category. Based on the 14 elements of service studied, service procedure is the element with the highest index value with the value of IKM of 62.00 and is at the level of less good. While the element with the lowest index value is the element of service cost certainty with an IKM value of 43.50 and is at the level of less good.